1970
DOI: 10.1002/qua.560040106
|View full text |Cite
|
Sign up to set email alerts
|

Study of the electronic structure of alternant radicals by the DODS method

Abstract: AbstractsThe polarization of closed shells in an alternant radical due to the field of its unpaired electron is discussed. It is shown that the Hartree-Fock solution is unstable relative to a small perturbation caused by polarization of closed shells in a long polyene radical. Its ground state is found to be antiferromagnetic with a forbidden zone in the spectra of one-particle excitations.On discute la polarisation des couches complttes dans un radical alternant due au champ de l'tlectron ctlibataire. On dtmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1972
1972
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 12 publications
(3 reference statements)
0
9
0
Order By: Relevance
“…We first consider the chain without bond alternation. Substituting the function 0 () nn gE from (6) into (14),…”
Section: Single Substitutionmentioning
confidence: 99%
See 4 more Smart Citations
“…We first consider the chain without bond alternation. Substituting the function 0 () nn gE from (6) into (14),…”
Section: Single Substitutionmentioning
confidence: 99%
“…From the analysis of the occupation numbers of natural orbitals calculated from UHF wave functions before and after projection, it was shown that the evaluation of the spin density after projection can be performed practically without loss of accuracy from non-projected values multiplied by / ( 1)  SS [57]. It was shown that this rule is asymptotically exact at  N [6,10,105].…”
Section: Properties Of Solutions Of the Generalized Hartree-fock Ementioning
confidence: 99%
See 3 more Smart Citations